Pengaruh Variasi Produk, Brand Image dan Co-Branding terhadap Keputusan Pembelian Produk Miniso: (Studi pada Konsumen Miniso Central Park di Jakarta Barat) - Sarah Pirmauli Sinaga; Rina Ayu Vildayanti (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This study aims to examine the influence of Product Variation, Brand Image, and Co-Branding on Purchase Decisions among Miniso Central Park consumers in West Jakarta. The research was conducted using a quantitative approach with 100 respondents selected through non-probability sampling with an accidental sampling technique. Data were collected using questionnaires based on a Likert scale and analyzed using SPSS version 25 with multiple linear regression. The findings show that Product Variation does not significantly influence purchase decisions, indicating that the wide variety of Miniso products alone is not the primary factor driving consumer choices. In contrast, Brand Image demonstrates a strong and significant influence, highlighting that consumers’ trust and perception of Miniso’s brand identity play an important role in their purchasing behavior. Furthermore, Co-Branding also significantly affects purchase decisions, as collaborations with other well-known brands or icons enhance the appeal and perceived value of Miniso products. The combined effect of Brand Image and Co-Branding creates stronger consumer engagement, although Product Variation alone remains insufficient in driving decisions. This study contributes to the understanding of retail marketing strategies, particularly in the context of lifestyle-oriented retail businesses. It suggests that building a strong brand image and leveraging effective co-branding partnerships are more impactful than merely expanding product variety. The implications of this research can assist retail companies in optimizing their marketing mix strategies to strengthen competitiveness in Indonesia’s rapidly growing retail sector.